2020
DOI: 10.1155/2020/8874468
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics-Based Simulation of Crop Canopy Temperature and Humidity in Double-Film Solar Greenhouse

Abstract: The microenvironment of the crop area in a greenhouse is the main factor that affects its growth, quality, and pest control. In this study, we propose a double-layer film solar greenhouse microenvironment testing system based on computational fluid dynamics simulations of a celery canopy with a porous medium. A real greenhouse was examined with a sensor system for soil, air, radiation, and carbon dioxide detection to verify the simulation results. By monitoring the internal environment of celery canopies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The CFD study has allowed the study of almost all existing passive greenhouse models worldwide, and has also been implemented as a tool for the optimization of climate management in greenhouses with active climate control [18][19][20]. There are currently a considerable number of studies applied to agricultural investors that have used CFD simulation to analyze thermal distribution [10,21,22], moisture distribution [5,21,23], efficiency of heating systems [24][25][26], the operation of cooling systems [27][28][29] and the microclimate generated as a function of different ventilation configurations [7,12,[30][31][32]. In the specific case of Colombia, the use of CFD and other modelling techniques to determine the behavior of the main greenhouse structures used has been carried out for the specific conditions of the Bogotá savannah and for a topography of flat soils, which is where the ornamental and cut flower industry is generally developed [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The CFD study has allowed the study of almost all existing passive greenhouse models worldwide, and has also been implemented as a tool for the optimization of climate management in greenhouses with active climate control [18][19][20]. There are currently a considerable number of studies applied to agricultural investors that have used CFD simulation to analyze thermal distribution [10,21,22], moisture distribution [5,21,23], efficiency of heating systems [24][25][26], the operation of cooling systems [27][28][29] and the microclimate generated as a function of different ventilation configurations [7,12,[30][31][32]. In the specific case of Colombia, the use of CFD and other modelling techniques to determine the behavior of the main greenhouse structures used has been carried out for the specific conditions of the Bogotá savannah and for a topography of flat soils, which is where the ornamental and cut flower industry is generally developed [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the floor temperature was respectively 5.2°C, 4.6°C and 2.0°C higher than that of the soil in the adjacent reference greenhouse after heat storage in clear, cloudy and overcast sky in winter (Wang et al, 2006). Moreover, the temperature and humidity distribution of the canopy in double film solar greenhouse was studied based on computational hydrodynamics, and the simulation results showed high agreement with the measured values (Jiao et al, 2020). Between double polyethylene films with liquid foam during the day when solar radiation was high.…”
Section: Introductionmentioning
confidence: 79%
“…Plant models involve various kinds of physical models, going from molecular and metabolic processes ( Farquhar et al., 1980 ), hydraulic functioning ( De Swaef et al., 2022 ), to soil and atmospheric physics ( Liu et al., 2020b ). Modern (functional-structural) plant modeling involves advanced physics simulation such as ray tracing to assess radiation ( De Visser et al., 2014 ; Bailey, 2018 ; Retkute et al., 2018 ) and computational fluid dynamics ( Bartzanas et al., 2013 ; Jiao et al., 2020 ). The latter are often computationally demanding and might require appropriate tools, such as surrogate modeling (discussed later), to make them feasible for, e.g., greenhouse control.…”
Section: Nine Simulation Intelligence Motifs For Plant Sciencementioning
confidence: 99%